Identification and Characterization of HtsA, a Second Heme-Binding Protein Made by Streptococcus pyogenes - Lei, Benfang (American Society for Microbiology, 2003)
Group A streptococci (GAS) can use heme and hemoproteins as sources of iron. However, the machinery for heme acquisition in GAS has not been firmly revealed. Recently, we identified a novel heme-associated cell surface protein (Shp) made by GAS. The shp gene is cotranscribed with eight downstream genes, including spy1795, spy1794, and spy1793 encoding a putative ABC transporter (designated HtsABC). In this study, spy1795 (designated htsA) was cloned from a serotype M1 strain, and recombinant HtsA was overexpressed in Escherichia coli and purified to homogeneity. HtsA binds 1 heme molecule per molecule of protein. HtsA was produced in vitro and localized to the bacterial cell surface. GAS up-regulated transcription of htsA in human blood compared with that in Todd-Hewitt broth supplemented with 0.2% yeast extract. The level of the htsA transcript dramatically increased under metal cation-restricted conditions compared with that under metal cation-replete conditions. The cation content, cell surface location, and gene transcription of HtsA were also compared with those of MtsA and Spy0385, the lipoprotein components of two other putative iron acquisition ABC transporters of GAS. Our results suggest that HtsABC is an ABC transporter that may participate in heme acquisition in GAS.